2015
DOI: 10.1177/0975425315591425
|View full text |Cite
|
Sign up to set email alerts
|

Informal Rental Housing Typologies and Experiences of Low-income Migrant Renters in Gurgaon, India

Abstract: A significant proportion of the working poor in Asian cities live in slums as renters. An estimated 60–90 per cent of low-income rentals in Asia are in the informal sector; 25 per cent of India’s housing stock comprises informal rentals. Yet informal rentals remain an understudied area. Through an empirical study, this article illustrates the typologies of informal rental housing in urban villages and unauthorized colonies in Gurgaon, a city of 1.2 million located within India’s National Capital Region (NCR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 6 publications
(6 reference statements)
0
25
0
Order By: Relevance
“…At a broader level, it can be argued that informal settlement and slums emerge as a response to the incapacity of formal institutions and policies of the State to provide basic human needs and rights including adequate housing within the formal market [13,21,33]. Conversely, such inability can be seen as performing a valuable opportunity in facilitating affordable housing for millions of poorer residents [34]. What is clear in their proliferation is that there is a positive correlation with poverty as where poverty exists, so do enclaves of informal and sub-standard housing [35].…”
Section: The Diverse Challenges Of Informal Settlements and Slumsmentioning
confidence: 99%
“…At a broader level, it can be argued that informal settlement and slums emerge as a response to the incapacity of formal institutions and policies of the State to provide basic human needs and rights including adequate housing within the formal market [13,21,33]. Conversely, such inability can be seen as performing a valuable opportunity in facilitating affordable housing for millions of poorer residents [34]. What is clear in their proliferation is that there is a positive correlation with poverty as where poverty exists, so do enclaves of informal and sub-standard housing [35].…”
Section: The Diverse Challenges Of Informal Settlements and Slumsmentioning
confidence: 99%
“…Similar to the bedas, these are one-room rental accommodations with shared bath and toilet facilities, but they are spread over a much smaller space and located in areas with diverse income and occupational profiles, unlike the concentrated pockets of industrial workers in Ludhiana. Other studies have found similar forms of rental housing for migrants in the National Capital Region (Naik 2015). Workers were also found to be residing in bastis, what are administratively known as jhuggi-jhopri clusters in Delhi.…”
Section: South Asia Multidisciplinary Academic Journal 19 | 2018mentioning
confidence: 63%
“…States often use informality 'as an instrument of both accumulation and authority' by the wilful change of land use often in contravention to the state's own laws. Failure of urban planning, in accommodating these migrants, is evidenced by the poor infrastructure and inadequate quality of life where they live in crowded, poorly lit and unventilated rooms (Naik, 2015), making them more vulnerable to such pandemics. For IIMA  INDIA…”
Section: Repopulating Urban Informalities: Inevitable Actions To Revive the Economymentioning
confidence: 99%